Chronic pulmonary aspergillosis may cause eosinophilic granulomatosis with polyangiitis via allergic bronchopulmonary aspergillosis. Issue 2 (16th February 2019) - Harada, Masanori; Imokawa, Shiro; Miwa, Satoru; Nihashi, Fumiya; Aono, Yuya; Amano, Yusuke; Uto, Tomohiro; Sato, Jun; Suda, Takafumi
Abstract: An 84-year-old man visited our hospital with a prolonged productive cough. Chest computed tomography showed a thick wall cavity and bilateral consolidations. Laboratory findings revealed peripheral blood eosinophilia, increased total IgE and elevated myeloperoxidase anti-neutrophil cytoplasmic antibody. Specific IgE and IgG antibodies and an immediate skin reaction against Aspergillus showed positive results. The histological findings of the lung parenchyma were compatible with eosinophilic pneumonia and bronchial biopsy showed eosinophilic vasculitis. Bronchoalveolar lavage fluid culture yielded Aspergillus fumigatus . These results met the diagnosis criteria for both allergic bronchopulmonary aspergillosis (ABPA) and eosinophilic granulomatosis with polyangiitis (EGPA). This case thus suggests that A. fumigatus might be a pathogen common to both diseases, and prolonged exposure to A. fumigatus in some patients with ABPA may promote progression to EGPA.